Implementasi Metode Elias Gamma Dalam Kompresi Iklan Pada Website PT. HWI - Amri Syahputra, Khairul (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Advertising is a marketing communication message or public communication about a product that is conveyed through a medium, financed by a known initiator, and addressed to part or all of the community. PT. HWI is a company engaged in marketing using a network marketing business system. PT. HWI also uses advertising promotions through available websites to attract potential customers to use their services. However, there are so many advertisements on websites such as images and videos, and this can take up storage space on web hosting. One way that this problem can be resolved, because using data compression can minimize a file size in the form of an image or video from the ad. The purpose of this study is to apply the Elias Gamma method in order to determine the compression performance if it is done by compressing website advertisements in the form of images, so that the large images will be compressed into a smaller size, so that the transmission process is carried out faster and reduces the location of data storage.